SHIFTING THE MEANING OF TABUH RAH BECOMES TAJEN (CHICKEN FIGHTING) IN BALI (THE PERSPECTIVE OF MAX SCHELER'S HIERARCHY OF VALUES) - Gede Agus Siswadi (UHN I Gusti Bagus Sugriwa Denpasar, 2023)
Bali has kept various forms of unique traditions, different from other regions. Like one of them is thetradition of tabuh rah. This tradition is part of a ritual or yajna carried out by the Balinese Hinducommunity. In this tradition, the facilities used are two roosters pitted against each other. The bloodfrom the chicken will be used as a tabuh rah. However, the tabuh rah ritual has changed its meaningto become tajen. Several factors influence this change and one of them is the implementation of ahobby owned by Balinese men, which is known as a bebotoh hobby. This article explores the valuesin the shift in meaning from the tabuh rah ritual to the tajen by using the philosophical hermeneuticmethod from data obtained through library research. The results of this study are 1). The valuecontained in the tabuh rah ritual can be explained in the form of Max Scheler's hierarchy of values.The highest value is the values of the holy as a sacred ritual and aims to perfect the animal's spiritto be sacrificed. The spiritual value seen from the tabuh rah ritual is the implementation oftantrayana teachings. The vital value can be seen from the purpose of the tabuh rah ritual as theimplementation of the Tri Hita Karana teachings last is the value of pleasure. 2). There is a shift invalues from the tabuh rah ritual to tajen. 3). The value to be achieved in tajen is the value of pleasure,which is a form of channelling a hobby and wanting to win from the gamble. Thus, other values areneglected.